P0620OXIDANT-INDUCED RENAL PRECONDITIONING BIOMARKERS FOR AKI PREVENTION WITH RBT-1. (6th June 2020) - Zager, Richard; Johnson, Ali; Ruiz, Stacey; Guillem, Alvaro; Keyser, Jeff; Rasmussen, Henrik; Singh, Bhupinder
Abstract: Background and Aims: Ischemic preconditioning has shown tissue protective effects in various organs including kidneys in animal models. However, the translation of these findings to human acute kidney injury (AKI) has not been successful, at least partly because of difficulty in simulating an ischemic state, as attempted by remote ischemic preconditioning (RIPC). RBT-1 is a novel therapeutic composed of SnPP (tin protoporphyrin) and FeS (iron sucrose) and was designed to induce non-ischemic, oxidant renal preconditioning to prevent AKI. It has shown efficacy in various models of AKI: glycerol-induced (rhabdomyolysis), maleate (ATP depletion), ischemia/reperfusion (I/R), and post-AKI progression to CKD (long-term progression). This study investigated the mechanism of action of RBT-1 in mice, and its translation to the clinical setting. Method: Male CD-1 mice were pretreated with control or RBT-1 for 18 hours; animals were then sacrificed for assessment of biomarkers of cytoprotection. Nrf2-/- mice were treated for 18 hours with RBT-1 prior to indication of ischemia/reperfusion (I/R); AKI was assessed by blood urea nitrogen (BUN) and plasma creatinine (PCr). Patients with CKD (Stage 3 and 4) were enrolled in Phase 1 studies of FeS and SnPP and cytoprotective biomarkers were assessed. Results: In mice, RBT-1 significantly increased several Nrf2-dependent antioxidant, anti-inflammatory genes, such as HO-1, NQO1, SRXN1, and GCLC. RBT-1 also increased cytoprotective heavy chain ferritin (Fhc) levels. Nrf2-/- mice were resistant to RBT-1-mediated protection against AKI. At baseline, CKD patients had elevated plasma HO-1 and urinary NQO1 levels. Ferritin and hemopexin levels were also elevated at baseline. RBT-1 components were shown to further increase HO-1, NQO1, ferritin, and hemopexin in patients with CKD. Conclusion: RBT-1 represents a novel therapeutic approach for the prevention of AKI. It mediates kidney protection by upregulating antioxidant and anti-inflammatory genes. Translation of RBT-1-mediated upregulation of cytoprotective markers has been demonstrated in the clinic in patients with CKD. These data, along with the broad range of RBT-1 activity previously shown in various models of AKI, highlight the potential of RBT-1 in AKI and suggest oxidant-induced renal preconditioning may be protective in preventing AKI.